Changes in the Behavior of Children Facing the Law After Guidance from the Class II Special Child Development Institute (LPKA) Banda Aceh - Saputra, Hijrah (CV. Literasi Indonesia, 2024)
Children's behavior is basically very easy to change according to what they learn, both positive and negative. So in this case, coaching is needed as an effort to control the child's behavior to make the child even better. For Children in Conflict with the Law (ABH), it is hoped that after leaving the coaching institution they will be able to behave better and function socially in society. The discussion in this research focuses on finding changes in children's behavior in dealing with the law after coaching from the Class II Special Child Development Institute (LPKA) Banda Aceh. This research uses a qualitative approach using a phenomenological approach to see the process of changing children's behavior in dealing with the law when they are in society. Data collection was carried out by observation, interviews, and documentation. The research results show that ABH has received full guidance and supervision during training at LPKA Class II Banda Aceh and has experienced positive changes such as acting well and being active in society. However, after the training that children receive, most of them apply positive activities in life. Not only positive changes, negative things will come back from the child's character, and their behavior can even repeat itself due to external factors, especially a lack of guidance and control from the family. After the guidance from the LPKA for Children in Conflict with the Law is no longer under the authority of the LPKA, but the guidance will be continued by the Correctional Center.